Between anti-communist hysteria and anti-yankee resentment. Salvador Abascal and cold war scenarios in Mexico (2015)
The goal of this article consists in analyzing the doctrinal position of a twentieth century Mexican right wing representative regarding the bipolarity of the Cold War.This was the case of Salvador Abascal Infante (1910 – 2000), intellectual and reactionary, who analyzed the Mexican twentieth century in each of his works, and judged it as an era of moral decadence due to the inluence of unbelief and the battle against Catholicism that, in his opinion, were carried out by the Mexican Revolution and the governments of the post revolution, particularly the Presidency of LázaroCárdenas (1934 – 1940). In this sense, Abascal Infante typiied the government of Cárdenas as part of the expansion of “international communism”, and, at the same time, execrated the inluence of the United States, as a Jewish and protestantnation, over Mexico and the world. Confronted with Cold War scenarios, this public leader discredited both communism and the United States for “threatening”, the catholic integrity of the country, in several ways.